Optimization of the Results of Surgical Treatment of Parasagittal Meningiomas of the Brain (Texas Journal of Medical Science, 2022)
According to literature data, meningiomas account for 18-34% of primary brain tumors, second in frequency only to tumors of the neuroectodermal series. According to various authors, brain tumors develop annually in 2-25 per 100,000 population. Despite the great successes and achievements in neurosurgery of parasagittal meningiomas, the problem of their surgical treatment is still relevant all over the world due to the development of both frequent intra- and postoperative complications, the high frequency of their recurrence, which in turn leads to the need for re-operations. All this affects the quality of life of patients. This article presents an analysis of the results of surgical treatment of this category of patients using radiation therapy for complex treatment.